Kekuatan Politik Perempuan dalam Organisasi Partai Keadilan Sejahtera (PKS) di Kabupaten Gorontalo - Walahe, Dewi (Universitas Gorontalo, 2018)
The purpose of this study is to know the political power of women in the organization of Prosperous Justice Party (PKS) in Gorontalo District. The research method used is quantitative method, and research type is descriptive. Data collection using questionnaires, interviews, observation and documentation. The research informant is the leader of the PKS Party of Gorontalo district. The result of the research shows that 1) the representation of women in the governance of the PKS party in Gorontalo Regency has not been able to fulfill womens representation 30% in the management of political parties according to Law no. 2 Year 2008 Jo. Law no. 2 Year 2011 on Political Parties. 2) There are four factors that inhibit the fulfillment of 30% of womens representation until it is not fulfilled: First, from the normative point, the Law regulating it is Law no. 2 Year 2008 Jo. UU no. 2 Year 2011 on political parties is not effective in the implementation process. Second, the cultural factor, patriarchal culture, where is men have a higher position than women; third, the Political Party Factor itself. The party sometimes never gives women the opportunity to occupy strategic positions in party stewardship so women are sometimes overlooked; and fourth, the factor of the womans personal. Indonesian women are still a lot of pessimists or feel afraid of themselves.